Selected Aspects of Heat Transfer Study in a Gun Barrel of an Anti-Aircraft Cannon - Mateusz ZIELIŃSKI; Piotr KONIORCZYK; Zbigniew SURMA; Marek PREISKORN; Judyta SIENKIEWICZ (Problemy Mechatroniki)
The paper presents the results of computer simulations of the transient heat flow in the barrel wall of a 35 mm caliber cannon for a single shot and a sequence of seven shots for a selected 30HN2MFA barrel steel. It was assumed that the inner surface of the barrel does not have a protective layer of chromium or nitride. When calculating heat transfer in a barrel, constant and temperature variable values of thermal conductivity, specific heat and density (in the range from RT (Room Temperature) up to 1000) in the 30HN2MFA steel were assumed. The test results were compared for both cases. A barrel with a total length of 3150 mm was divided into 6 zones (i = 1,, 6) and in each of them, the heat flux density was calculated as a function of the time q _i (t) on the inner surface of the barrel. In each zone, the heat transfer coefficient, as a function of the time hi(t) and bore gas temperature as a function of the time Tg(t) to the cannon barrel for given ammunition parameters, was developed. A calculating time equaling 100 ms per single shot was assumed. The results of the calculations were obtained using FEM implemented in COMSOL Multiphysics ver. 5.6 software.